Tissue Immune Cells Fuel Obesity-Associated Inflammation in Adipose Tissue and Beyond - Liu, Rui; Nikolajczyk, Barbara S. (Frontiers in Immunology, 2019)
Obesity-associated inflammation stems from a combination of cell-intrinsic changes of individual immune cell subsets and the dynamic crosstalk amongst a broad array of immune cells. Although much of the focus of immune cell contributions to metabolic disease has focused on adipose tissue-associated cells, these potent sources of inflammation inhabit other metabolic regulatory tissues, including liver and gut, and recirculate to promote systemic inflammation and thus obesity comorbidities. Tissue-associated immune cells, especially T cell subpopulations, have become a hotspot of inquiry based on their contributions to obesity, type 2 diabetes, nonalcoholic fatty liver diseases and certain types of cancers. The cell-cell interactions that take place under the stress of obesity are mediated by intracellular contact and cytokine production, and constitute a complicated network that drives the phenotypic alterations of immune cells and perpetuates a feed-forward loop of metabolic decline. Herein we discuss immune cell functions in various tissues and obesity-associated cancers from the viewpoint of inflammation. We also emphasize recent advances in the understanding of crosstalk amongst immune cell subsets under obese conditions, and suggest future directions for focused investigations with clinical relevance.